1999
DOI: 10.1007/s004020050021
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of high-standing greater trochanter

Abstract: Eleven patients with high-standing greater trochanter (13 joints) aged 13-36 years underwent surgery. Distal transfer of the greater trochanter (group T) was performed in 4 patients (5 joints) and lateral displacement osteotomy (group L) in 7 (8 joints). The average follow-up duration was 13.4 years in group T and 5.9 years in group L. Clinical results were evaluated by the hip score according to Merle d'Aubigne. The mean hip score in group T was 13.4 points before operation and 15.4 points after operation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Lateral displacement of the greater trochanter has been described as the most important component of the trochanteric transfer [17,26,30], as distal displacement alone does not increase the lever arm of the abductors. Further, distal transfer alone changes the resultant vector of the forces acting on the hip to a more vertical position, increasing the pressure over a reduced area of the joint and possibly accelerating the development of osteoarthritis The articulotrochanteric distance and centrotrochanteric distance are negative on the preoperative radiograph, and a small trochanteric offset can be seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lateral displacement of the greater trochanter has been described as the most important component of the trochanteric transfer [17,26,30], as distal displacement alone does not increase the lever arm of the abductors. Further, distal transfer alone changes the resultant vector of the forces acting on the hip to a more vertical position, increasing the pressure over a reduced area of the joint and possibly accelerating the development of osteoarthritis The articulotrochanteric distance and centrotrochanteric distance are negative on the preoperative radiograph, and a small trochanteric offset can be seen.…”
Section: Discussionmentioning
confidence: 99%
“…This deformity is termed coxa brevis [5,25], high-standing greater trochanter [26] or relative trochanteric overgrowth [6,13,23], and occurs as a sequela of diseases such as developmental dysplasia of the hip, slipped capital femoral epiphysis, infections of the hip, and Legg-Calvé-Perthes disease. In this situation the hip abductors habitually become functionally insufficient owing to the reduction of their resting length and lever arm [20].…”
Section: Introductionmentioning
confidence: 99%
“…8 Morscher's 3 parallel osteotomies 7 for restoring normal proximal femoral anatomy can be performed in children with a Trendelenburg gait and limited abduction after the ossification of the greater trochanter. 3,4,7,8,[20][21][22][23] Morscher osteotomy reduced the mean CTD from 33 to 7 mm. 20 It achieved good results in 32 of 37 patients with no or little arthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…10 A plate with angle blade has been used for collodiaphysis osteosynthesis, and tensionband wiring is added for greater trochanter osteosynthesis. 4,[20][21][22][23] In our study, a custom-made locked proximal femoral plate with a trochanteric hook was used to stabilise trochanteric osteotomy. Although a trochanteric proximal femur plate has been used in paediatrics, it is not appropriate for adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Relative neck lengthening morbidity is not higher than for surgical dislocation alone; this aspect may increase the biomechanical value of the procedure. Lateral displacement of the greater trochanter has been described as the most important component of the trochanteric transfer [34,35]. Those authors suggested that distal displacement alone does not increase the lever arm of the abductors and distal transfer alone increases the pressure over a reduced area of the joint, possibly accelerating the development of osteoarthritis [36].…”
Section: Indications and Drawbacksmentioning
confidence: 99%